Donation and Tax Compliance - Jaensirisak, Sirirut (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
This article intended to explore information from past academic papers and relevant laws as well as discussed Tax rulings of the Revenue Department from January 1999 to September 2012. The discussion focused on rulings related to donation allowances under Personal Income Tax in order to inform taxpayers who were subject to Personal Income Tax (PIT) and intended to donate their wealth to organizations and other social charities. Donation is one of the important allowances for PIT calculation and also a part of social contribution. Taxpayers should clearly understand the conditions under which donation is allowed by law, tax ruling, judgments and other documents for the purpose of accuracy in tax calculation. From past events of misconception by taxpayers and also fake proofs of donation in order to save paying tax, Revenue Department officers should be more careful to realize and be concerned about giving clear information to taxpayers, as well as establishing guidelines for prevention and detection of illegal acts.